Entrepreneurial Decision Making among Students - Oktaviani, Rizki; Gumala Sari, Egi; Ningsih, Sri (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
This study aims to examine the effect of accounting information systems, the use of e-commerce, and customer experience on entrepreneurial decision making by accounting students in Bekasi City Universities. This study uses a quantitative approach with a sample of 8 universities in Bekasi City. Data were collected through a questionnaire to 86 respondents using the snowball sampling method. Data analysis was carried out using the SEM-PLS (Partial Least Squares) technique. The results showed that accounting information system has a positive effect on entrepreneurial decision making, e-commerce has a positive effect on entrepreneurial decision making, then customer experience has a positive effect on entrepreneurial decision making. This study is limited to a sample from universities in Bekasi City, so the results many not fully represent the general population of accounting students. Future research could expand the sample size, examine a broader geographical context, or explore other relevant variables. This study provides important insights into the factors that encourage accounting insights to start a business, as well as enriching the literature related to the application of technology and customer experience in the context of student entrepreneurship.